Addressing gender-based violence in Peru: Citizenship and critical issues. The Women's Emergency Center (CEM) technicians’ point of view - del Pino Espejo, Maria José; Sánchez-Tovar, Ligia; Soto Arango, Diana Elvira; Villalba, Karina (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2021)
Objective: To understand critical issues faced by the technical staff working in the Women's Emergency Centers (CEM) in Peru, when assisting women victims of gender violence.  Originality/support: Valuable information is provided on the assistance provided to women victims of gender-based violence in the MECs. This information is very useful for decision making, aimed at improving the work and effectiveness of the performance of the technicians in the centers. It highlights a situation that has been little studied and serves as a reference for other realities in the international Latin American context. Method: A qualitative research approach was used to inform the proposed aims. Forty-one technicians from the Women's Emergency Centers (CEM) in Peru participated in the study. The results revealed that the critical issues perceived by the technical staff were working with material and travel limitations, work overload that made it difficult to care for victims, delays in the treatment of cases of gender-based violence and revictimization of the victim. In addition, dealing with a macho cultural framework that masks the situations and with religious and linguistic diversity. Conclusions: It is concluded that it is necessary to view gender violence with a focus on citizenship and gender justice that under the principles of equality, respect for human rights and defense of cultural diversity, without incurring in a paternalistic action.